New species of Corotoca Schiødte, 1853 from South America and description of first instar larva - Zilberman, Bruno; Casari, Sônia A. (Zootaxa, 2018)
Corotoca Schiødte, 1853 is a Neotropical genus of termitophile beetles, with five species. The establishment of this genus marks the first record of insects living associated to termites. A new species, Corotoca pseudomelantho Zilberman, sp. nov. from Brazil and Argentina, based on adult and first larval instar, is described and illustrated. The first instar larva of C. melantho Schiødte, 1853, a related species, is redescribed and illustrated. This is the first record of Corotoca species from Argentina.